Transient osteomyelitis of the distal radius in a three-year-old patient - Giuseppe Rinonapoli; Michele Bisaccia; Luigi Meccariello; Giovanni Battista Mancini; Flavia Marrani; Predrag Grubor; Giuseppe Rollo; Auro Caraffa (Medicinski glasnik, 2019)
Aim: Reporting on an atypical case of a three-year-old patient affected by osteomyelitis of the distal radius, completely healed without antibiotic therapy. Methods: The clinical case is related to a three-year-old patient, whose clinical picture began with fever, pain and swelling of the right wrist. After three days, fever and swelling disappeared, but pain persisted. Plain x-rays of the right wrist, hematologic analyses, magnetic resonance imaging (MRI) with contrast medium and biopsy were performed in order to make a differential diagnosis between acute osteomyelitis and a malignant neoplasm, i.e. Ewing's sarcoma. Results: The plain x-rays of the right wrist showed an osteolytic area of the distal radio, with blurred rim. Haematology showed high erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP); MRI confirmed the presence of a lesion, of no certain origin, therefore a biopsy was done. The histology was that of an inflammatory tissue. The patient, after the biopsy, was completely asymptomatic, ESR and CRP were back to normal. Before starting antibiotic therapy, it was preferred repeating x-rays. From the latter, the osteolysis completely disappeared. On the basis of the x-rays, blood exam and symptomatology, it was decided not to submit the patient to any treatment. After two years, the patient never had similar episodes. Conclusion: Patient presented with all characteristics of an osteomyelitis of distal radius, was unexpectedly spontaneously healed, without antibiotic therapy. Two years after the onset of the disease the patient recovered without clinical and radiographic sequelae. No similar cases are found in the literature .
Keywords: bone healing; infection; long bone; physis; paediatrics; radius